Neonatal outcome of maternal premature rupture of membranes more than 18 hours - Shakya, Amshu; Gupta, Sweta Kumari (Journal of Kathmandu Medical College, 2020)
Background: Premature Rupture of Membranes has been known to complicate pregnancy since ages. Several risk factors may be associated with occurrence of premature rupture of membranes. It is associated with varied neonatal complications, neonatal sepsis and prematurity being the most hazardous ones. Objectives: This study was conducted to evaluate the incidence of neonatal sepsis following premature rupture of membranes, risk factors and neonatal complications associated with premature rupture of membrane of more than 18 hours in the neonates admitted in a tertiary care center. Methodology: Descriptive observational study was undertaken for 18 months from August 2013 to January 2015 in the College of Medical Sciences, Chitwan, Nepal. This study included 82 neonates admitted to the Neonatal Intensive Care Unit with maternal history of premature rupture of membranes of more than 18 hours with medical conditions excluded. Results: The incidence of premature rupture of membranes in this hospital was 8.9%. Frequently associated maternal risk factors were history of prior abortion (16, 19.5%), urinary tract infection (7, 8.5%), and antecedent coitus (7, 8.5%). In the study population, 68 (83%) neonates had complications and 14 (17%) neonates had no complication. The incidence of neonatal sepsis following PROM in present study was 6.1%. Neonatal sepsis was significantly associated with chorioamnionitis (p<0.001). The most frequently occurring complication was probable neonatal sepsis (53, 64.6%), followed by prematurity (31, 37.8%) and perinatal asphyxia (15, 18.3%). There was a directly proportional relation of neonatal sepsis, chorioamnionitis, respiratory distress syndrome and mortality with duration of premature rupture of membranes. Conclusion: Commonly occurring maternal risk factors with PROM were prior abortion, UTI and antecedent coitus. In the study population, infectious morbidity was highest. Chorioamnionitis was significantly associated with culture proven neonatal sepsis. Prolonged duration of premature rupture of membranes increased the risk of neonatal sepsis, meningitis, respiratory distress syndrome and perinatal death. Prevention of these risk factors, appropriate and timely management including improved obstetric and neonatal care can provide intact survival of the neonates.